THE STUDENT COLLABORATIVE WRITING ACTIVITY THROUGH GOOGLE DOCS - Mulyani; Syatriana , Eny; Ul Haq, Muhammad Zia (FKIP Unismuh Makassar, 2024)
The main problem in this research was to find out two research objectives, are to find out the implementation of writing descriptive text using the Google Docs Applications, and to find out the students' perceptions of implementing Google Docs in students' descriptive text on collaborative writing in SMP 13 Makassar. This research used a descriptive qualitative approach. The participant of this study was a 7th-grade level who used the Google Docs application as collaborative learning to write a descriptive text. The data in this study was collected through checklist observations and questionnaires. Based on research, this study shows how students use Google Docs to create descriptive text. Authors exchange accounts with their partners for reading and editing. The study also revealed that the study had a beneficial effect on students' answers. The final, students can afford and like to use this learning tool well. This shows that using Google Docs for group writing in the descriptive text is successful.